1991
DOI: 10.1002/prot.340110204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of the three‐dimensional structure of human interleukin‐4

Abstract: The structure of human interleukin 4 (IL-4) was predicted utilizing a series of experimental and theoretical techniques. Circular Dichroism (CD) spectroscopy indicated that IL-4 belonged to the all alpha-helix class of protein structures. Secondary structure prediction, site-directed mutagenesis, and CD spectroscopy suggested a predominantly alpha-helical structure, consistent with a four-helix bundle structural motif. A human/mouse IL-4 chimera was constructed to qualitatively evaluate alternative secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 29 publications
(2 reference statements)
2
14
0
Order By: Relevance
“…This has begun to change-algorithms directed at predicting the secondary structure locations in a/a proteins are more accurate than their unbiased counterparts (Kneller et al, 1990;Presnell et al, 1992). In a prediction of the structure of IL-4 (Curtis et al, 1991) in advance of the NMR structure determination (Smith et al, 1992), the helical regions of this a / a protein were predicted with 90% fidelity. Second, peptide fragment databases of the types constructed by Unger et al (1989) or Rooman et al (1992) could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…This has begun to change-algorithms directed at predicting the secondary structure locations in a/a proteins are more accurate than their unbiased counterparts (Kneller et al, 1990;Presnell et al, 1992). In a prediction of the structure of IL-4 (Curtis et al, 1991) in advance of the NMR structure determination (Smith et al, 1992), the helical regions of this a / a protein were predicted with 90% fidelity. Second, peptide fragment databases of the types constructed by Unger et al (1989) or Rooman et al (1992) could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Tertiary structures were generated by investigating the plausible arrangements of the a-helices via a combinatorial packing approach (20,34). This approach was developed based on the original concept of the packing of a-helices proposed by Crick (35).…”
Section: Methodsmentioning
confidence: 99%
“…Although the problem ofpredicting protein structure from the amino acid sequence information alone remains unsolved, recent advances in secondary and tertiary structure prediction of proteins have shown that reasonable structures can often be proposed by using a heuristic approach in conjunction with experimental data (18). For all-a-helical proteins, this approach has been applied to generate low-resolution structural models for a number of proteins (19)(20)(21). Some of the structural features proposed by these methods have been verified by subsequent x-ray or NMR experiments (22).…”
mentioning
confidence: 99%
“…In the present article, residues are numbered from the N-terminal Glu as residue 1, so that the natural IL-4 sequence starts at residue 5 . In addition, the two potential N-linked glycosylation sites at Asn 42 and Asn 109 in the natural sequence were changed to Asp by site-directed mutagenesis to prevent hyperglycosylation in the yeast host (Curtis et al, 1991). Samples for NMR contained 2 mM 15N-or l3C/I5N-labeled IL-4, pH 5.7, dissolved in either 90% Hz0/10% D2O or 99.996% D2O.…”
Section: Methodsmentioning
confidence: 99%